Investigating the illicit market in veterinary medicines: An exploratory online study with pet owners in the United Kingdom - Pons-Hernandez, Monica (Trends in organized crime, 2023)
The illicit market in veterinary medicines is an overlooked issue despite threatening the health of non-human and human animals. It is thought to be increasing within the major markets of the global North due to the growth of e-commerce and social media sites. This paper examines the online market in illicit veterinary medicines through an exploratory study of the public’s online experiences as pet owners in the UK. To this end, we collected data through literature-based research and an online survey. Drawing on Passas’ criminogenic asymmetries framework, the research found that the confluence of legal, political, cultural, economic and knowledge asymmetries likely facilitate the market in illicit veterinary medicines in the UK. Our research concludes that, while previous reports suggest the illicit market is dominated by medicines to treat pets, it increasingly consists of medicines for farmed animals. This brings its own set of challenges and risks, and a pressing need for further research on the market’s dynamics.